Unequal origins : immigrant selection and the education of the second generation - Feliciano, Cynthia, 1973- (New Americans (LFB Scholarly Publishing LLC), 2006)
Feliciano examines how immigrants compare to those left behind in their origin countries, and how that selection affects the educational adaptation of children of immigrants in the United States. Her findings contradict the assumption that immigrants are negatively selected: nearly all immigrants are more educated than the populations in their home countries, but Asian immigrants are the most highly selected. This helps explain the Asian second generations superior educational attainment as compared to Europeans, Afro-Caribbeans, or Latin Americans. The book challenges cultural explanations for ethnic differences by highlighting how inequalities in the relative pre-migration educational attainments of immigrants are reproduced among their children in the U.S. --